Things That Go Bump in the Literature: An Environmental Appraisal of “Haunted Houses” - Dagnall, Neil; Drinkwater, Kenneth G.; O’Keeffe, Ciarán; Ventola, Annalisa; Laythe, Brian; Jawer, Michael A.; Massullo, Brandon; Caputo, Giovanni B.; Houran, James (Frontiers in Psychology, 2020)
This paper contains a narrative overview of the past 20-years of environmental research on anomalous experiences attributed to “haunted houses.” This exercise served as a much-needed update to an anthology of noteworthy overviews on ghosts, haunts, and poltergeists (Houran & Lange, 2001b). We also considered whether new studies had incorporated certain recommendations made in this anthology. Our search revealed a relative paucity of studies (n = 66) on environmental factors that ostensibly stimulate haunt-type experiences. This literature was diverse and often lacked methodological consistency and adherence to the prior suggestions. However, critical consideration of the content revealed a recurring focus on six ambient variables: embedded (static) cues, lighting levels, air quality, temperature, infrasound, and electromagnetic fields. Their relation to the onset or structure of witness reports showed mostly null, though sometimes inconsistent or weak outcomes. However, such research as related to haunts is arguably in its infancy and new designs are needed to account better for environmental and architectural phenomenology. Future studies should therefore address four areas: (i) more consistent and precise measurements of discrete ambient variables; (ii) the potential role of “Gestalt influences” that involve holistic environment-person interactions; (iii) individual differences in attentional or perceptual sensitivities of percipients to environmental variables; and (iv) the role of attitudinal and normative influences in the interpretation of environmental stimuli. Focused scrutiny on these issues should clarify the explanatory power of evolutionary-environmental models for these and related anomalous experiences.